Emission from the working and counter electrodes under co-reactant electrochemiluminescence conditions. Issue 28 (25th June 2021) - Adamson, Natasha S.; Theakstone, Ashton G.; Soulsby, Lachlan C.; Doeven, Egan H.; Kerr, Emily; Hogan, Conor F.; Francis, Paul S.; Dennany, Lynn
Abstract : Exploration of potential-dependent, multi-colour co-reactant electrochemiluminescence from multiple luminophores at the working and counter electrodes reveals new pathways to emission. Abstract : We present a new approach to explore the potential-dependent multi-colour co-reactant electrochemiluminescence (ECL) from multiple luminophores. The potentials at both the working and counter electrodes, the current between these electrodes, and the emission over cyclic voltammetric scans were simultaneously measured for the ECL reaction of Ir(ppy)3 and either [Ru(bpy)3 ] 2+ or [Ir(df-ppy)2 (ptb)] +, with tri- n -propylamine as the co-reactant. The counter electrode potential was monitored by adding a differential electrometer module to the potentiostat. Plotting the data against the applied working electrode potential and against time provided complementary depictions of their relationships. Photographs of the ECL at the surface of the two electrodes were taken to confirm the source of the emissions. This provided a new understanding of these multifaceted ECL systems, including the nature of the counter electrode potential and the possibility of eliciting ECL at this electrode, a mechanism-based rationalisation of the interactions of different metal-complex luminophores, and a previously unknown ECL pathway for the Ir(ppy)3 complex at negative potentials that was observed even in the absence of the co-reactant.